MODEL SUPERVISI AKADEMIK DALAM MENINGKATKAN KINERJA GURU - Zulfiani Zulfiani; Hisban Thaha; Hilal Mahmud (Institut Agama Islam Negeri (IAIN) Palopo, 2021)
This study describes the principal's supervisory model in improving teacher performance, the stages of principal supervision in improving teacher performance, and the obstacles faced in implementing principal supervision in improving teacher performance. This research is a descriptive qualitative research with pedagogical approach, psychological approach, sociological approach and managerial approach. The research was conducted at SMP Negeri 8 Palopo. Data sources are primary and secondary sources. Data collection techniques used observation, interviews, and documentation. The research instruments were interview guidelines, observation sheets and documentation. The data is processed by editing, coding, and tabulation. Data were analyzed by data reduction, data display, and conclusions. Testing the validity of the data was carried out through triangulation of techniques and triangulation of sources. The results showed that the supervision models used were conventional models, artistic models, scientific models and clinical models. The stages of supervision, namely the planning stage, include socialization, explaining supervision indicators, and making schedules, the implementation stage includes pre-observation, observation and post-observation activities, and finally the follow-up stage. Obstacles in implementing supervision are the broad managerial scope of school principals, teachers lack of preparation for learning, high supervisor teacher subjectivity, frequent replacement of school principals, limited facilities and infrastructure, and lack of teacher discipline.